2017
DOI: 10.1063/1.4992058
|View full text |Cite|
|
Sign up to set email alerts
|

Continuous point-like high-temperature laser discharge produced by terahertz free electron laser

Abstract: A continuous point-like laser discharge of record high temperature has been produced in argon at atmospheric pressure with focusing of the radiation of the Novosibirsk terahertz free electron laser (NovoFEL). According to spectral measurements, the temperature in the center of the millimeter-sized plasma sphere was 28000 K at a plasma density of 1.5×1017 cm-3 and an average NovoFEL power of 200 W at a wavelength of 130 μm (2.3 THz).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…In the very first experiments, the previously established fact [16] was confirmed that the discharge in pure homogeneous inert gases, despite its dazzling brightness and external effect (figure 1), has a standard average temperature for laser discharges of 8000-9000 K (0.7-0.8 eV) (figure 2). Such a discharge is of definite interest in visible spectroscopy as a bright source of a continuous spectrum.…”
Section: Experiment: Setup Methods and Main Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…In the very first experiments, the previously established fact [16] was confirmed that the discharge in pure homogeneous inert gases, despite its dazzling brightness and external effect (figure 1), has a standard average temperature for laser discharges of 8000-9000 K (0.7-0.8 eV) (figure 2). Such a discharge is of definite interest in visible spectroscopy as a bright source of a continuous spectrum.…”
Section: Experiment: Setup Methods and Main Resultsmentioning
confidence: 58%
“…Obviously, for increase in the discharge temperature, it is necessary to somehow limit the plasma volume and bind it to the radiation focus. The simplest version of such a system was implemented in [16]. Argon was injected into air at atmospheric pressure as a jet directed at the focus at 90 • to the radiation.…”
Section: Experiment: Setup Methods and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…And the ongoing research is aimed at demonstrating an increase in the efficiency of the EUV radiation yield with an increase in the heating radiation frequency. Previously [51], it was demonstrated that using NovoFEL radiation it is possible to maintain a point-like discharge in an argon jet with a plasma density of 10 17 cm −3 . In this case, the temperature of the electrons was low (2-3 eV), since the discharge was ignited in a jet admitted to the air at atmospheric pressure and was equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies may also be of interest for possible applications of the THz discharge. This discharge is currently considered as a possible powerful source of UV (ultraviolet), VUV (vacuum UV), and EUV (extrime UV) radiation [7,29,51]. The dense plasma of a terahertz plasma torch is considered as an active medium for various plasma-chemical reactors [52].…”
Section: Thz Discharge Propagation In Noble Gasesmentioning
confidence: 99%